2021
DOI: 10.1155/2021/6635964
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of CNN and RNN for Voice Pathology Detection

Abstract: Diagnosis on the basis of a computerized acoustic examination may play an incredibly important role in early diagnosis and in monitoring and even improving effective pathological speech diagnostics. Various acoustic metrics test the health of the voice. The precision of these parameters also has to do with algorithms for the detection of speech noise. The idea is to detect the disease pathology from the voice. First, we apply the feature extraction on the SVD dataset. After the feature extraction, the system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…This data is a collection of vowels /a/, /i/, and /u/ and “Good Morning, how are you?” sentences, recorded with normal, low, high, rising, and falling pitch, available in both English and German languages. However, utilizing the /a/ vocalization subset of SVD remarks good classification results and is used in the literature [ 35 , 55 ]. For our analysis, we have used the /a/ vowel phonation with a normal pitch in the English language.…”
Section: Methodsmentioning
confidence: 99%
“…This data is a collection of vowels /a/, /i/, and /u/ and “Good Morning, how are you?” sentences, recorded with normal, low, high, rising, and falling pitch, available in both English and German languages. However, utilizing the /a/ vocalization subset of SVD remarks good classification results and is used in the literature [ 35 , 55 ]. For our analysis, we have used the /a/ vowel phonation with a normal pitch in the English language.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians have been using sounds and acoustic data such as acoustic data to diagnose various conditions: voice pathologies, dry and wet cough, sleep disorders, and more [28][29][30][31][32][33][34] . Recently, several works also exploited sound data for large-scale COVID screening.…”
Section: Related Workmentioning
confidence: 99%
“…We determined that the CNN approach was more appropriate for the current dataset as we had a limited number of samples from which we aimed to test our model. Previous work by You, Liu and Chen [32] observed that more complicated neural networks (i.e., RNNs and/or hybrid models) may result in lower accuracy and/or fail to converge when trying to model "relatively" small datasets and Zhang et al [29] observed that RNNs are more computationally expensive compared to CNNs, with potentially little increases in accuracy [33]. Therefore we implemented a convolutional neural network (CNN) model for voice samples machine learning training, which relied on image feature transformation (see [34] for a similar example).…”
Section: Feature Extractionmentioning
confidence: 99%